2007
DOI: 10.1016/j.humpath.2007.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the mTOR pathway in sporadic angiomyolipomas and other perivascular epithelioid cell neoplasms

Abstract: Angiomyolipomata (AML) belong to a family of tumors known as perivascular epithelioid cell tumors (PEComas) that share a common immunophenotypic profile of muscle and melanocytic differentiation. These tumors are clonal in nature and have a strong association with tuberous sclerosis. Genetic analyses have reported allelic imbalance at the TSC2 locus on 16p13. In the context of non-TSC, non-LAM associated AMLs and non-renal PEComas, the functional status of the TSC2 signaling pathway has not been reported. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
149
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 44 publications
10
149
0
5
Order By: Relevance
“…1,2 The pathogenesis of angiomyolipoma is determined by mutations affecting TSC genes, with eventual deregulation of the RHEB/MTOR/ RPS6KB2 pathway. 3 It has been observed that angiomyolipomas regressed somewhat during sirolimus therapy, an MTOR inhibitor, but tended to increase in volume after the therapy was stopped. 4 Histologically, the common angiomyolipoma is characterized by the presence of a variable mixture of fat, spindle and epithelioid smooth muscle cells, and abnormal thick-walled blood vessels.…”
mentioning
confidence: 99%
“…1,2 The pathogenesis of angiomyolipoma is determined by mutations affecting TSC genes, with eventual deregulation of the RHEB/MTOR/ RPS6KB2 pathway. 3 It has been observed that angiomyolipomas regressed somewhat during sirolimus therapy, an MTOR inhibitor, but tended to increase in volume after the therapy was stopped. 4 Histologically, the common angiomyolipoma is characterized by the presence of a variable mixture of fat, spindle and epithelioid smooth muscle cells, and abnormal thick-walled blood vessels.…”
mentioning
confidence: 99%
“…This association is significantly stronger for the two members of the family AML and LAM. Kenerson et al [5] using western blotting and immunohistochemistry demonstrated upregulation of the mTOR signalling pathway with negative feedback inhibition of AKT, consistent with functional loss of TSC1/2 in sporadic renal AMLs and non-renal PEComas.…”
Section: Discussionmentioning
confidence: 73%
“…Genetic analysis demonstrated that the mTOR pathway is activated in PEComas 9 and therefore mTOR inhibitors (such as temsirolimus and rapamycin) have been administered in clinical trials to patients at higher risk with encouraging results. 10 In our case, the diagnosis of PEComa avoided an improper indication to chemotherapy for recurrent GCT, which could be indicated based only on clinical findings.…”
Section: Discussionmentioning
confidence: 99%